2007
DOI: 10.1177/15910199070130s111
|View full text |Cite
|
Sign up to set email alerts
|

Venous Anatomy of the Sphenoparietal Sinus: Evaluation by MR Imaging

Abstract: The termination of the superficial middle cerebral vein (SMCV) has been described as entering or being partially equivalent to the venous sinus coursing under the lesser sphenoid wing, which has classically been called the sphenoparietal sinus. However, the recent literature reports that the SMCV is not connected to the sphenoparietal sinus. In this study, the venous anatomy was evaluated to clarify the anatomy of the sphenoparietal sinus and the termination of the SMCV. Magnetic resonance imaging (MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…San Millán Ruíz et al (38) investigated the venous anatomy of this region in 15 nonfixed cadavers and found no connection between the SMCV and the sphenoparietal sinus in any specimen. Similarly, in the findings from a study by Takahashi et al (39), the SMCV was not connected with the sphenoparietal sinus at contrast-enhanced 3D fast spoiled gradient-echo T1-weighted MR imaging in any of 24 patients. In contrast, other investigators have found a high incidence of connection between the sphenoparietal sinus and the SMCV (32,33,37).…”
Section: Smcv and Sphenoparietal Sinussupporting
confidence: 62%
See 1 more Smart Citation
“…San Millán Ruíz et al (38) investigated the venous anatomy of this region in 15 nonfixed cadavers and found no connection between the SMCV and the sphenoparietal sinus in any specimen. Similarly, in the findings from a study by Takahashi et al (39), the SMCV was not connected with the sphenoparietal sinus at contrast-enhanced 3D fast spoiled gradient-echo T1-weighted MR imaging in any of 24 patients. In contrast, other investigators have found a high incidence of connection between the sphenoparietal sinus and the SMCV (32,33,37).…”
Section: Smcv and Sphenoparietal Sinussupporting
confidence: 62%
“…It connects to the branches of the middle meningeal vein laterally and ends at the anterior aspect of the cavernous sinus medially. The sphenoparietal sinus receives venous drainage from the nearby skull base, namely, from a diploic vein of the orbital roof, a diploic vein of the greater sphenoid wing, and, occasionally, an orbital vein (37)(38)(39).…”
Section: Smcv and Sphenoparietal Sinusmentioning
confidence: 99%
“… 12 , 14 , 15) Our general understanding of the sphenoparietal sinus is that it is a large meningeal channel that runs medially just below the lesser sphenoid wing to empty into the anterior part of the CS, usually the SMCV flows into this sinus. 2) However, Ruíz et al 15) and Takahashi et al 18) recently questioned this classical understanding of the sphenoparietal sinus. They described two independent venous channels (the sinus of the lesser sphenoid wing and the SMCV) that exist in this region, and they found no connections between these two venous channels.…”
Section: Venous Drainage Into the Cs From Different Structuresmentioning
confidence: 99%
“…15) It drains diploic veins from the orbital roof and the greater sphenoid wing without venous connection to the SMCV. 15 , 17 , 18) The CS has connections medially to the opposite side of the CS through intercavernous sinuses. Green 46) described that anterior and posterior intercavernous sinuses receive some osseous veins from the lateral part of the posterior clinoid plate.…”
Section: Venous Drainage Into the Cs From Different Structuresmentioning
confidence: 99%
“…The MMV is depicted to run within the grooves of the skull with the accompanying MMA, and is partly drained into the sphenoparietal sinus and the emissary veins through the foramen spinosum. 10 One previous study histologically confirmed and precisely described the MMA and MMV running side by side nearby the foramen spinosum and pterion, and running separately at the parietal bone. 11 Our case highlights the anatomy of the course of the MMV, and the proximity of the MMA and MMV near the foramen spinosum.…”
Section: Discussionmentioning
confidence: 79%